Pancreatic Metastasis from Colon Carcinoma Treated with Radiotherapy with Palliative Benefit - Saif, Muhammad Wasif; Kaley, Kristin (JOP. Journal of the Pancreas, 2010)
No absreact available. Image: Milstein Hospital. New York, NY, USA.